Outsourcing w działalności banków w kontekście orzecznictwa Trybunału Sprawiedliwości UE i interpretacji art. 43 ust. 13 ustawy o podatku od towarów i usług - Knawa, Katarzyna (Kwartalnik Prawa Podatkowego, 2015)
This article is aimed to summarise the achievements of jurisprudence of the European Union Court of Justice regarding exemption of actions which are distinct as a whole, are specific and perform essential functions of the exempt service. The CJEU judgements have been implemented in Poland through Article 43 section 13 of the Statute on Value Added Tax. The indeterminate terms used in the provision are however the source of controversies and contrary interpretations in the tax practice and local jurisprudence. Some of them are clearly contrary to the theses presented by the CJEU, which entails breach of interpretation rule that requires local laws to be interpreted in the light of the EU provisions. It is true that the CJEU judgements can be disregarded while interpreting local laws however only to the extent where the local law interpretation is more favourable for the taxpayer. Should the interpretation narrowed the scope of exemption as compared to the point of view presented by CJEU the Polish court is obliged to examine local provisions in the light of the UE one. Thus the Polish courts are in particular obliged to explore the meaning of the UE law provision as interpreted by the respective CJEU judgements and compare the result with the Polish law interpretation. Therefore it seems to be necessary to remind the source of Article 43 section 13 of the statute on Value Added Tax and to systematise notions on how this provision should be construed in the light of the EU law.